Adoption and use of information and communications technology in rural councils: a case of Nyanga rural district council - Manyevere, Yemurai (Midlands State University, 2017)
The rise and rapid advances in information and communication technologies (ICTs) has been at the centre of global socio-economic revolutions. The use of these ICTs has become a vital component for business success in developed countries. ICTs affect the performance, growth, expansion and services delivery of any business or organization. However Zimbabwe is a developing country and as such lags behind in terms of ICT adoption. This study focused on ICT adoption and use in Rural Councils, using Nyanga Rural District Council as a case study. The research used mainly quantitative methodology were interviews and questionnaires were used to gather relevant information to the study. Various authorities were used as a guide to the study. The technology acceptance model (TAM) proposed that ICT adoption is mainly influence by perceived ease of use and perceived usefulness. The results suggest that perceived usefulness is more important in determining adoption of ICTs, that is, if the management of the organisation discover how ICTs can help their business they are more inclined to adopt it. However the study also revealed a number of factors that hinder the Rural Council from adopting ICTs that include the lack of training and the inability to use the technologies among others. This study also revealed the influence the semi-adoptive state was having on their clientele. The study recommended various ways that the council can communicate with their customers and other ways the council can integrate information technologies in their operations.